2007
DOI: 10.1584/jpestics.g06-27
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of selective disease controlling activity of mepanipyrim

Abstract: Mepanipyrim exhibited excellent disease control activity against Botrytis cinerea, but poor activity against Cochliobolus miyabeanus; however, the mycelial growth of C. miyabeanus was inhibited more strongly than that of B. cinerea. Therefore, disease control efficacy by mepanipyrim in vivo is not correlated with mycelial growth inhibition in vitro. While mepanipyrim prevented pectinase secretion in B. cinerea at 0.1-1 mg/ml, it did not interfere with secretion in C. miyabeanus, even at 100 mg/ml, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several analogues (e.g., cyprodinil and Pyrimethanil) are also in agricultural use. Their mode of action is (a) inhibition of specific amino acid biosynthesis and/or (b) inhibition of protein sequestration ,, . The major mode of action of mepanipyrim is proposed to be the inhibition of pathogenicity-related protein secretion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analogues (e.g., cyprodinil and Pyrimethanil) are also in agricultural use. Their mode of action is (a) inhibition of specific amino acid biosynthesis and/or (b) inhibition of protein sequestration ,, . The major mode of action of mepanipyrim is proposed to be the inhibition of pathogenicity-related protein secretion .…”
Section: Introductionmentioning
confidence: 99%
“…Their mode of action is (a) inhibition of specific amino acid biosynthesis and/or (b) inhibition of protein sequestration ,, . The major mode of action of mepanipyrim is proposed to be the inhibition of pathogenicity-related protein secretion . Mepanipyrim is quite a safe compound (acute oral LD 50 > 5000 mg kg −1 , rat) suggesting the least harmful effects on human or animal health, and several toxicological studies were reported − , .…”
Section: Introductionmentioning
confidence: 99%